The putative role of neuroinflammation in the complex pathophysiology of migraine: From bench to bedside - Leonardo Biscetti; Elena Cresta; Letizia Maria Cupini; Paolo Calabresi; Paola Sarchielli (Neurobiology of Disease, 2023)
The implications of neurogenic inflammation and neuroinflammation in the pathophysiology of migraine have been clearly demonstrated in preclinical migraine models involving several sites relevant in the trigemino-vascular system, including dural vessels and trigeminal endings, the trigeminal ganglion, the trigeminal nucleus caudalis as well as central trigeminal pain processing structures. In this context, a relevant role has been attributed over the years to some sensory and parasympathetic neuropeptides, in particular calcitonin gene neuropeptide, vasoactive intestinal peptide and pituitary adenylate cyclase-activating polypeptide. Several preclinical and clinical lines of evidence also support the implication of the potent vasodilator and messenger molecule nitric oxide in migraine pathophysiology. All these molecules are involved in vasodilation of the intracranial vasculature, as well as in the peripheral and central sensitization of the trigeminal system. At meningeal level, the engagement of some immune cells of innate immunity, including mast-cells and dendritic cells, and their mediators, has been observed in preclinical migraine models of neurogenic inflammation in response to sensory neuropeptides release due to trigemino-vascular system activation. In the context of neuroinflammatory events implicated in migraine pathogenesis, also activated glial cells in the peripheral and central structures processing trigeminal nociceptive signals seem to play a relevant role. Finally, cortical spreading depression, the pathophysiological substrate of migraine aura, has been reported to be associated with inflammatory mechanisms such as pro-inflammatory cytokine upregulation and intracellular signalling. Reactive astrocytosis consequent to cortical spreading depression is linked to an upregulation of these inflammatory markers. The present review summarizes current findings on the roles of immune cells and inflammatory responses in the pathophysiology of migraine and their possible exploitation in the view of innovative disease-modifying strategies.